2021
DOI: 10.1371/journal.pone.0255086
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study on the readiness of dental, medical, and nursing students for interprofessional learning

Abstract: Background Interprofessional education (IPE) is crucial in dentistry, medicine, and nursing. However, scant mixed methods studies have compared the IPE outcomes across these disciplines to develop evidence-based IPE. This study explored the differences in the readiness of dental, medical, and nursing students for interprofessional learning before and after IPE workshops and elucidated reasons for this disparity. Methods Data were obtained from dental, medical, and nursing students who participated in IPE wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In the present study, signi cant changes were observed in the teamwork and collaboration subscale for students who participated, regardless of whether they were EOL cases. Similar effects of RIPLS have been observed in other EOL studies [29] and interprofessional work case studies [30]. This supports our result that case study and group discussion are effective for building teamwork and collaboration within the medical college for education in multiple professions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, signi cant changes were observed in the teamwork and collaboration subscale for students who participated, regardless of whether they were EOL cases. Similar effects of RIPLS have been observed in other EOL studies [29] and interprofessional work case studies [30]. This supports our result that case study and group discussion are effective for building teamwork and collaboration within the medical college for education in multiple professions.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the pre-test, the post-test RIPLS scores of both groups signi cantly increased to a mean (± SD) 78.87 ± 8. 30…”
Section: Effects On Readiness For Interprofessional Learning Scalementioning
confidence: 99%
“…The finding of this study of a positive association between centrality and students' academic performance was consistent with prior studies in medical and dental education. 9,30,31 Because teamwork is emphasized in health care 3 and health care education, 32 centrality may play an important role in achieving optimal academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health professionals can provide professional oral healthcare to prevent aspiration pneumonia and postoperative complications [ 8 10 ]. Therefore, both dental and nursing students need to learn about oral healthcare, nursing care, and interprofessional communication skills and to understand interprofessional healthcare practices [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that IPE between oral health professionals and nurses has a beneficial impact on students’ understanding of team medicine [ 17 – 22 ]. However, there are few studies and reports on IPE in Japan [ 11 , 23 ]. Moreover, to our knowledge, no studies of IPE programmes have included a combination of nursing care training and oral healthcare training.…”
Section: Introductionmentioning
confidence: 99%